The synaptonuclear messenger RNF10 acts as an architect of neuronal morphology - Carrano, Nicolò; Samaddar, Tanmoy; Mauceri, Daniela (Molecular neurobiology, 2019)
The Ring Finger Protein 10 [RNF10] is a novel synapse-to-nucleus signaling protein that specifically links activation of synaptic NMDA receptors to modulation of gene expression. RNF10 dissociation from the GluN2A subunit of the NMDA receptor represents the first step of its synaptonuclear transport and it is followed by an importin-dependent translocation into the nucleus. Here, we have identified protein kinase C [PKC]-dependent phosphorylation of RNF10 Ser31 as a key step for RNF10 detachment from NMDA receptor and its subsequent trafficking to the nucleus. We show that pSer31-RNF10 plays a role both in synaptonuclear signaling and in neuronal morphology. In particular, the prevention of Ser31 RNF10 phosphorylation induces a decrease in spine density, neuronal branching, and CREB signaling, while opposite effects are obtained by mimicking a stable RNF10 phosphorylation at Ser31. Overall, these results add novel information about the functional and structural role of synaptonuclear protein messengers in shaping dendritic architecture in hippocampal neurons.